NEO PRAGMATISME RICHARD RORTY DAN FENOMENA CHILDFREE PASANGAN MUSLIM - Mafiah, Yeni (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2024)
The phenomenon of childfree has not only become a western culture, but has spread and developed even in the Muslim-majority country of Indonesia. The purpose of this study is to examine the phenomenon of childfree in Muslim couples and find its correlation with Richard Rorty's Neo Pragmatism. The type of research is library research that uses a qualitative approach. The results of his research are, there are several Muslim couples who are married, choosing not to have children or childfree. There are two factors that make couples choose childfree, namely external factors and internal factors. External factors, including poor economic conditions, difficulty finding work, inadequate living facilities, national policy, individualism, community irreligion and influence of western mindsets on changes in the value of children in the family. Internal factors include the couple's attitude towards their partner's choice, decision maturity and family experience. This fact proves that the thinking of Muslim couples has now begun to leave traditionalist thinking and turn to modernism. Neo-pragmatism prioritises the importance of individual choice in determining one's own values and behaviour without being bound by existing dogmas or norms, so Rorty's understanding can be used to better understand and respect Muslim couples who decide not to have children.